The Role of Family Firms Heterogeneity on the Internationalisation and Performance Relationship - Rienda, Laura; Andreu, Rosario (European Journal of Family Business, 2021)
Many papers have addressed the influence of different characteristics of family businesses on strategic decisions, including those of internationalisation. However, little is known about the relationship between the internationalization of family firms and firm profitability. For this reason, from the socioemotional wealth perspective, in this paper, we focus on the moderating role of some heterogeneous characteristics of family firms on the relationship between internationalisation and business performance. Specifically, we analyse a sample of 76 companies belonging to the Spanish hotel industry, one of the most internationalised sectors and with a large presence of family businesses. The results show that family involvement in ownership and management, as well as generation, moderates the relationship between internationalisation and profitability in the Spanish hotel industry.